2022
DOI: 10.3389/fimmu.2022.865425
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Profiling Identifies Serum Biomarkers in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) causes serious disability and productivity loss, and there is an urgent need for appropriate biomarkers for diagnosis, treatment assessment, and prognosis evaluation. To identify serum markers of RA, we performed mass spectrometry (MS)-based proteomics, and we obtained 24 important markers in normal and RA patient samples using a random forest machine learning model and 11 protein–protein interaction (PPI) network topological analysis methods. Markers were reanalyzed using additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Proteomics is a powerful screening tool for serum biomarkers in various diseases which may aid in our understanding of the pathogenesis and pathophysiology of a disease through identification of disease-associated protein profiles. 22 24 Disease biomarkers may serve as agents for diagnostics or directly serve as targets for therapeutic treatment. Previous proteomic studies have successfully identified protein signatures in the serum of noninfectious uveitis that can predict the relative need for IMT.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics is a powerful screening tool for serum biomarkers in various diseases which may aid in our understanding of the pathogenesis and pathophysiology of a disease through identification of disease-associated protein profiles. 22 24 Disease biomarkers may serve as agents for diagnostics or directly serve as targets for therapeutic treatment. Previous proteomic studies have successfully identified protein signatures in the serum of noninfectious uveitis that can predict the relative need for IMT.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 16 , 39 Alterations in circulating proteins have been documented in a variety of inflammatory diseases, and serum proteomics offers insights into the pathophysiology of the disease, aids in disease diagnosis, tracks disease advancement, and predict the prognosis. 20 , 40 , 41 Diorio et al 42 identified fms-like tyrosine kinase 3 and mast cell immunoglobulin-like receptor 1 as predictive biomarkers of severe cytokine release syndrome and found IL18 as a possible targetable cytokine in immune effector cell–associated neurotoxicity syndrome by serum proteomics. However, there are no clear results regarding serum protein expression profiles of eCRSwNP patients and the association between differentially expressed proteins and eosinophilic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples were collected from patients with CRSwNP in the discovery cohort, and serum proteomics analysis was conducted using liquid chromatography-tandem mass spectrometry (LC-MS/MS) as previously outlined. 20 , 29 Briefly, serum samples were processed to extract total proteins, and their concentration was determined using the BCA assay. Subsequently, 100 μg of protein underwent acetone precipitation, followed by redissolution, reduction, alkylation, protein digestion, and final peptide desalting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study suggested ORM1 in serum as a differentially expressed protein that was found to be correlated with disease activity. 123 Acute appendicitis. Acute appendicitis is one of the most prevalent abdominal illnesses on a global scale having a 7-8% lifetime risk according to estimates.…”
Section: Diagnostic and Prognostic Biomarker For Other Diseasesmentioning
confidence: 99%